Anabolic effect of human parathyroid hormone fragment on trabecular bone in involutional osteoporosis: a multicentre trial. - Reeve, J (1980)
After baseline studies, 21 patients with osteoporosis were treated with human parathyroid hormone fragment (PTH 1-34) given as once-daily subcutaneous injections for 6-24 months. The dose used did not cause hypercalcaemia even in the first few hours after injection. Calcium and phosphate balances improved in some patients, but there was no significant improvement in the group values. There were, however, substantial increases in iliac trabecular bone volume: the mean increase, confirmed by repeat blind measurements, was 70% above mean baseline volume. The new bone was histologically normal. Those patients who had the largest increases in 47Ca-kinetic and histomorphometric indices of new bone formation showed the greatest increases in trabecular bone volume, suggesting that treatment with human parathyroid hormone fragment caused a dissociation between formation and resorption rates that was confined to trabecular bone. Since vertebrae are four-fifths composed of trabecular bone, this hormone fragment may prove useful in treating patients with the crush fracture syndrome.